Impact of Preclinical Labor and Delivery Shadowing on Student Perceptions of Obstetrics and Gynecology as a Specialty and Possible Career: A Prospective Cohort - Dotters-Katz, Sarah K.; Smid, Marcela C.; Tinkham, Sara; Chuang, Alice (American Journal of Perinatology Reports, 2019)
Objective The purpose of this study was to determine the impact of preclinical shadowing on student interest and perceptions of obstetrics and gynecology (OBGYN).Methods We enrolled a prospective cohort of preclinical medical students who shadowed on labor and delivery (L&D). Students sent electronic surveys a week prior (presurvey), the week after (postsurvey), and three months after shadowing (far-survey). Responses compared using descriptive statistics. We analyzed common themes of free text responses.Results From July 2016 to April 2017, 41 students shadowed on L&D; 81% were female. Eighty percent responded to at least one survey, 37% completed all surveys, (presurvey: 76%, postsurvey: 51%, and far-survey: 46%). Prior to shadowing, 10% (3/31) planed a career in OBGYN compared with 24% (5/21) after shadowing (p = 0.42). Over 50% of students described the people and procedures as altering their perceptions of OBGYN in a positive way. Common themes explaining this change included: culture (n = 4), team interactions (n = 4), seeing deliveries (n = 3), and hands-on experiences (n = 3). Three months after shadowing, 79% described the experience as very worthwhile. Eighty-nine percent would recommend the experience to a friend not interested in OBGYN and 100% stated they would shadow again.Discussion Although shadowing may not increase students' desire to pursue OBGYN, it is nearly universally felt to be worthwhile and improves perceptions of the field.
Keywords: labor and delivery; shadowing; preclinical exposure; medical students; perceptions; obstetrics; culture